2015
DOI: 10.1039/c5ob00791g
|View full text |Cite
|
Sign up to set email alerts
|

Screening of quinoline, 1,3-benzoxazine, and 1,3-oxazine-based small molecules against isolated methionyl-tRNA synthetase and A549 and HCT116 cancer cells including an in silico binding mode analysis

Abstract: Elevated activity of methionyl-tRNA synthetase (MRS) in many cancers renders it a possible drug target in this disease area, as well as in a series of parasitic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…K252a has also been reported to block leukemia inhibitory factor-induced STAT3 activation in olfactory receptor neurons (21). We have recently reported the synthesis and anticancer effect of various azaspirane derivatives and demonstrated their mechanism of action in several types of cancers (7,22,23). In our previous study, we reported the development of azaspirane based small molecule, 2-(1-(4-(2-cyanophenyl)1-benzyl-1H-indol-3-yl)-5-(4-methoxy-phenyl)-1-oxa-3-azaspiro(5,5)undecane (CIMO) and demonstrated inhibition of the JAK-STAT pathway in hepatocellular carcinoma (7).…”
Section: An Azaspirane Derivative Suppresses Growth and Induces Apoptmentioning
confidence: 99%
“…K252a has also been reported to block leukemia inhibitory factor-induced STAT3 activation in olfactory receptor neurons (21). We have recently reported the synthesis and anticancer effect of various azaspirane derivatives and demonstrated their mechanism of action in several types of cancers (7,22,23). In our previous study, we reported the development of azaspirane based small molecule, 2-(1-(4-(2-cyanophenyl)1-benzyl-1H-indol-3-yl)-5-(4-methoxy-phenyl)-1-oxa-3-azaspiro(5,5)undecane (CIMO) and demonstrated inhibition of the JAK-STAT pathway in hepatocellular carcinoma (7).…”
Section: An Azaspirane Derivative Suppresses Growth and Induces Apoptmentioning
confidence: 99%
“… [a] Paclitaxel represents the positive control and the IC 50 value of paclitaxel is taken from our previous report …”
Section: Resultsmentioning
confidence: 99%
“…The antiproliferative effect of triazolo-pyridines towards lung cancer cells were investigated by the MTT dye uptake method as described earlier. [41,42] Briefly, A549 cells (2.5 × 10 4 /ml) were incubated in triplicate in a 96-well plate in the presence or absence of the indicated concentrations of compounds in a final volume of 0.2 ml for different time intervals at 37°C. Thereafter, 20 μl of MTT solution (5 mg/ml in PBS) was added to each well.…”
Section: Mtt Assaymentioning
confidence: 99%
“…18,19,29,30 In addition, deletion or over-expression of FtsK can result in the inhibition of cell division. 20 The docking scores (DS) of the docked compounds with the FtsK motor domain are summarized in Table 7.…”
Section: Rationalization Of Putative Target Of the Bioactive Thiazolimentioning
confidence: 99%
“…Expansion of this chemotype enabled us to define the essential pharmacophore for Type III secretion inhibition by this structural class. 11,12 In a continuation of our work to synthesize and explore the pharmacological properties of various classes of heterocycles, [13][14][15][16][17][18][19][20] we report here the application of MoO 3 nanoparticles in the synthesis of novel thizolidin-4-ones, followed by their use as anti-bacterial agents against S. typhi and K. pneumoniae. Furthermore, we used chemogenomics approaches to predict protein targets in silico and rationalized the mode of action of the bioactive thiazolidin-4-one.…”
Section: Introductionmentioning
confidence: 99%